The Correlation Between Patient Knowledge About Triase Services With Anxiety Of Yellow Label Patients In Emergency Installation Pelabuhan Hospital Of Cirebon - Ahmad Priyadi; Hediyana Yusuf; Ahmad Syaripudin (LPPM ITEKES Mahardika, 2020)
On the yellow label of patient includes high priority is emergency victims who cannot be given the highest or moderate priority, patient care can be delayed in less than 30 minutes. The patient's ignorance about the management of triage services by nurses in the emergency room influences the patient's satisfaction and anxiety. This study aimed to determine the correlation between patient knowledge about triage services and the anxiety of yellow label patients in the Emergency of Pelabuhan Hospital in 2019. This is a correlational analytic research with cross sectional approach. The population in this study were all yellow label patients admitted to the Emergency Hospital of the Port Hospital at April. The number of patients in February 2019 was 616 patients. The number of samples was 86 respondents obtained by using the Slovin formula. Data collection used a questionnaire to measure knowledge variables and the Hamilton Rating Scale for Axiety (HRS-A) was used to measure the anxiety level Hawari (2014).Data were analyzed by univariate and bivariate using chi square. More than half of the respondents have less knowledge about triage, which is 49 respondents (57.0%). Most, but less than half experience severe anxiety or panic, as many as 32 respondents (37.2%). There is a significant correlation between the level of knowledge of patients about triage services and the anxiety of yellow label patients in the Emergency of Pelabuhan Hospital, as evidenced by the p value = 0.026 using fisher exact test